Diabetic retinopathy in early vs late-onset type 2 diabetes: prevalence and risk factors in Kuantan, Pahang - Md Aris, Mohd Aznan; Shamsudin, Nurzawani; Salam, Adzura; Mohd Rus, Razman (Faculty of Medicine, UKM, 2024)
Introduction: The incidence of type 2 Diabetes in Malaysia has been rising affecting younger individuals over the past years. Early onset type 2 Diabetes (EOT2D) refers to diabetes diagnosed before age of 40 years old. Diabetic retinopathy is the primary cause of vision loss in developed countries. The major objective of this study is to measure and compare the prevalence of diabetic retinopathy and its associated factors in patients with early onset and late onset type 2 diabetes mellitus who attended primary care in Kuantan. Materials and method: A cross sectional study was conducted at 4 selected government health clinics in Kuantan, Pahang. A total of 360 early onset and late type 2 diabetes patients were randomly selected. Latest fundus was taken using digital retinal imaging technology. Data collected include demographic, clinical parameter, cardiovascular risk factor with micro and macrovascular complication. Results: Our study revealed that the prevalence of diabetic retinopathy was significantly higher in early-onset type 2 diabetes (EOT2D) patients at 70.7% compared to 46.5% in late-onset type 2 diabetes (LOT2D) patients. In EOT2D patients, the duration of diabetes mellitus (DM), HbA1c levels, and diabetic kidney disease were significantly associated with the development of diabetic retinopathy. In contrast, for LOT2D patients, duration of DM and being female patients showed significant association with diabetic retinopathy. Conclusion: In conclusions, these findings underscore the greater risk and burden of diabetic complications faced by EOT2D patients, emphasizing the need for early and intensive management strategies to mitigate these risks and improve long-term health outcomes.